Survey on the Industry and Public Awareness on the Effects of Harmful Chemicals in Personal Care Products (PCPs) on Human and the Environment - Mohammad Anshor, Nur Azlin; Ab. Aziz, Nur Adila (Recent Trends in Civil Engineering and Built Environment, 2023)
People usually use personal care products (PCPs) daily for various purposes. It can be categorized into fragrances, deodorant, lotion, sunscreen, face wash, makeup, hair products, soaps, hand sanitizers and toothpaste. In Malaysia, the increasing growth rate of personal care products is because of the high awareness of the young generation towards hygiene, beauty, and self-images. However, some people do not know the destructive effect of using personal care products because of the harmful chemicals in the product. Therefore, this research investigates the implementation of public and industry about the danger of certain chemical substances in personal care products (PCPs) and determines the chemical substances commonly present in PCPs that affect humans and the environment in Malaysia. The questionnaire was designed based on the information and ideas gathered through the literature review to achieve the research objectives. Lectures and public people have reviewed the questionnaire to ensure the questionnaire is practical and easy for the public to answer. Section B and Section C on the questionnaire will be where the knowledge and implementation of public and industry people will be asked about the PCPs’ effect on them and the environment. The survey will be analyzed using the statistical function in Microsoft Excel, and it will be associated with Section A in a demographic profile questionnaire. The results showed that only a tiny percentage of the public (15%) and industry (4%) still lack knowledge on the issue. Between both sample populations, there is only have slight difference (0.3%) towards the implementation regarding the issue. The study is aimed to make the public more aware of checking the ingredients of chemical substances and get some research before purchasing and using the products as a precautionary measure for themselves and the environment.